2016
DOI: 10.1002/cmdc.201500394
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget Drugs: an Epigenetic Epiphany

Abstract: Epigenetics refers to changes in a biological phenotype that are not due to an underlying change in genotype. In eukaryotes, epigenetics involves a set of chemical modifications of the DNA and the histone proteins in nucleosomes. These dynamic changes are carried out by enzymes and modulate protein-protein and proteinnucleic acid interactions to determine whether specific genes are expressed or silenced. Both the epigenetic enzymes and recognition domains are currently important drug discovery targets, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 85 publications
2
61
0
4
Order By: Relevance
“…The preference of HDACi's structural elements among various epi‐drugs to design multitargeting agents is due to the following reasons: (i) in the 2000‐2010 years there was a boom of studies on HDACi by medicinal chemists belonging to both industrial and academic institutions, and many HDACi characterized by a wide structural variety have been reported; (ii) the cap group that characterizes all HDACi lays out of the catalytic tunnel of the enzymes and is tolerant of a high degree of structural variation without compromising the enzyme inhibition activity . This allows the introduction in this portion of a specific warhead able to interact with another target different from HDACs …”
Section: The Mtdl Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The preference of HDACi's structural elements among various epi‐drugs to design multitargeting agents is due to the following reasons: (i) in the 2000‐2010 years there was a boom of studies on HDACi by medicinal chemists belonging to both industrial and academic institutions, and many HDACi characterized by a wide structural variety have been reported; (ii) the cap group that characterizes all HDACi lays out of the catalytic tunnel of the enzymes and is tolerant of a high degree of structural variation without compromising the enzyme inhibition activity . This allows the introduction in this portion of a specific warhead able to interact with another target different from HDACs …”
Section: The Mtdl Approachmentioning
confidence: 99%
“…The polypharmacology approach was born with the aim to overcome the limitations of the single‐targeted therapy, such as the potential mechanism(s) of resistance caused by redundancy and robustness of biological pathways . Polypharmacology has the aim to simultaneously hit different targets, all related to the onset and development of a certain disease, although at different levels . Notably, polypharmacology is quite different from “compound promiscuity”.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, practice has shown that there is a poor correlation between in vitro drug effects and in vivo efficacy with target-driven approximations [2,3]. Our increasing understanding of the multiple interacting feedback mechanisms operating within the cell has led to the realization that polypharmacology (the interaction of a single drug on multiple targets or the use of multiple drugs on multiple targets) will be necessary to treat the majority of non-monogenic disorders [4][5][6][7].…”
Section: Opinionmentioning
confidence: 99%
“…Thus, epigenetic profiling of the brainstem of (sporadic) AD patients and its pairing with blood epigenetic signatures in the same individuals could potentially lead to the discovery of novel biomarkers that are able to detect either subtle changes at the very early stages of the disease, when the pathology is believed to be still reversible, or even an early peripheral response to AD pathology. Yet another exceedingly valuable asset of the study of epigenetic dysregulation in the brainstem is the fact that various pharmacological interventions impacting on either the epigenetic machinery ([161]; reviewed by Maloney and Lahiri [76]) or the 5-HT/NA system have already been developed and clinically approved; hence they could be implemented rapidly as a novel intervention for AD. Collectively, scrutinizing the interactions between the early AD-affected brainstem and the local epigenetic modifications will be of pivotal importance not only for understanding the pathogenesis of AD and the causal or consequential relationship of epigenetic alterations with AD, but also for the development of highly demanded early, reliable biomarkers and novel therapeutic strategies.…”
Section: Looking To the Futurementioning
confidence: 99%